Measurement of axonal excitability: Consensus guidelines. Issue 1 (January 2020) - Kiernan, Matthew C.; Bostock, Hugh; Park, Susanna B.; Kaji, Ryuji; Krarup, Christian; Krishnan, Arun V.; Kuwabara, Satoshi; Lin, Cindy Shin-Yi; Misawa, Sonoko; Moldovan, Mihai; Sung, Jiaying; Vucic, Steve; et al.
Highlights: Axonal excitability studies allow deductions about membrane and ion channel properties in vivo. Excitability studies have investigated nerve function and pathophysiology in neurological disease. Guidelines summarise physiological basis, methodology and interpretation of excitability studies. Abstract: Measurement of axonal excitability provides an in vivo indication of the properties of the nerve membrane and of the ion channels expressed on these axons. Axonal excitability techniques have been utilised to investigate the pathophysiological mechanisms underlying neurological diseases. This document presents guidelines derived for such studies, based on a consensus of international experts, and highlights the potential difficulties when interpreting abnormalities in diseased axons. The present manuscript provides a state-of-the-art review of the findings of axonal excitability studies and their interpretation, in addition to suggesting guidelines for the optimal performance of excitability studies.